Use of Magnetic Induction to Activate a "Touchless" Shape Memory Alloy Implantable Penile Prosthesis. Issue 4 (1st April 2019) - Le, Brian V.; McVary, Kevin T.; McKenna, Kevin; Colombo, Alberto
ABSTRACT: Introduction: We describe a novel physiologic penile prosthesis that uses shape memory alloy properties to mimic the transition between a flaccid and erect penis using magnetic induction instead of hydraulic pressure. Aim: To evaluate the parameters of magnetic induction to activate a shape memory alloy implantable penile prosthesis. Methods: We prototyped an implantable penile prosthesis cylinder using temperature-tuned nickel titanium alloy tubes laser cut to specifications. The device was then tested implanted in an animal tissue model and in cadaveric tissue. Testing consisted of placing the device deactivated in its more malleable and compressed state, then activating it using an external inducer wand while measuring temperature changes that occur on the surface of the device, within the tissue, and at the skin surface. Main Outcome Measures: Our main outcome measures were the efficiency of activation and thermal safety of this approach. Results: Using a handheld magnetic inductor, we were able to successfully activate the SMA penile prosthesis with no direct contact under 45 seconds. This handheld wand produced a magnetic field that penetrated tissue and caused the appropriate phase change within the prosthesis. Tissue temperature (middle and surface probes) in the animal tissue model increased only a few degrees Celsius during the activation process, and never exceeded 28 degrees Celsius from a baseline at room temperature ∼ 25 degrees Celsius. We encountered similar results without a notable change in tissue temperature in the cadaveric tests. The fully activated device resisted buckling forces of 2.66 kgf ± 0.045. Clinical Implications: This non-hydraulic shape memory prosthesis obviates the needs for reservoirs and pumps, and the wand-based interaction with the device may be easier to use. Strength & Limitations: This technology represents a fundamental departure from the hydraulic-based penile prosthesis and has comparable mechanical properties as current-marked devices. It appears to show thermal safety in controlled environments, however real-world use would need further studies. Further optimization of prototypes needs to be done prior to human clinical trials. Conclusion: A shape memory penile prosthesis is a promising alternative to hydraulic-based penile prostheses and can be activated safely and efficiently using magnetic induction in our models of the human penis.